Personal Unconsciousness in a Sun Movie - Anastasya, Elma; Chitra, Bima Prana; Zuindra, Zuindra (Kajian Linguistik dan Sastra, 2024)
This study aims to analyze the aspects and the impacts of personal unconscious are contributed to A-Ho's personality in A Sun movie by Chung Mong-Hong. This research is included in literary criticism, which uses psychoanalysis as a theoretical approach. The research objectives to find out aspects of personal unconscious affects A-Ho's personality in A Sun movie and analyze the impacts of personal unconscious contributed to A-Ho’s personality development. The researcher uses the archetypal theory by Carl Gustav Jung. The data of this study were taken from dialogues and narration in A Sun movie. The results of the analysis show about aspects of A Ho's personal unconscious which are the main reasons for the impact of changes in A Ho's personality. The second result of this study is the impact that occurred on A Ho's personality and personal change and development in A Ho who became better because of the life problems he lived. Abstrak Penelitian ini bertujuan untuk menganalisis aspek dan dampak ketidaksadaran pribadi yang berkontribusi terhadap kepribadian A-Ho dalam film A Sun karya Chung Mong-Hong. Penelitian ini termasuk dalam kritik sastra yang menggunakan psikoanalisis sebagai pendekatan teorinya. Tujuan penelitian untuk mengetahui aspek-aspek ketidaksadaran pribadi yang mempengaruhi kepribadian A-Ho dalam film A Sun dan menganalisis dampak ketidaksadaran pribadi yang berkontribusi terhadap perkembangan kepribadian A-Ho. Peneliti menggunakan teori arketipe Carl Gustav Jung. Data penelitian ini diambil dari dialog dan narasi dalam film A Sun. Hasil analisis menunjukkan tentang aspek ketidaksadaran pribadi A Ho yang menjadi penyebab utama dampak perubahan kepribadian A Ho. Hasil kedua dari penelitian ini adalah dampak yang terjadi pada kepribadian A Ho dan perubahan serta perkembangan diri A Ho yang menjadi lebih baik karena permasalahan hidup yang dijalaninya.